Examining the main Factors that Hinder the Transition of SOE’s To Sustainable Energy Supply in South African and Nigeria - Motswaledi , Thabang R.; Motloung, Sysman (Journal of Ecohumanism, 2025)
Ensuring a sustainable energy supply is a fundamental responsibility of state-owned enterprises (SOEs) as part of their public service mandate. However, in countries such as South Africa and Nigeria, which are vital economic hubs in Africa, the shift to sustainable energy supply has encountered significant challenges. Despite possessing the necessary infrastructure and financial capability to spearhead this shift, these countries have made minimal progress in establishing sustainable energy provision, resulting in an energy supply shortage. This paper seeks to investigate the primary factors impeding SOEs’ transition to sustainable energy supply in South Africa and Nigeria. Throughout the paper, the term "energy utility" is used interchangeably with "state-owned entity" (SOE), and "clean energy" is used interchangeably with "green energy" for clarity. This qualitative study draws on accredited journal articles, reports, and books to comprehend the issues at hand. The findings indicate that the government must take decisive action to tackle the challenges affecting SOE performance. Factors such as corruption, insufficient infrastructure investment, operations, and maintenance, and a lack of commitment to sustainable development policies must be addressed through good governance. In conclusion, the paper underscores factors such as the failure to integrate sustainable energy supply, issues of good governance, corruption, infrastructure development, sustainable development, and unequal access to energy as the primary obstacles hindering SOEs’ transition to sustainable energy supply.